Determination of the thermal diffusivity and the temperature profiles of the whole potato (Solanum tuberosum L.) during heating in a liquid medium - Moro Pisco, Jose Francisco
The objective of this work was to determine the thermal diffusivity of the potato and to model heat transfer and temperature in the potato (Solanum tuberosum L.) during heating in a liquid medium. Potatoes of the Yungay variety were used. The experimental methodology was carried out through five stages, such as: determination of the characteristic dimensions of the potato (equivalent diameter), determination of thermal diffusivity (α), experimental obtaining of the temperature at different positions within the potato with a temperature of liquid medium at 70 °C, modeling was done using the heat transfer equation by conduction in only one direction and the solution of said equation was performed using the methodology of finite differences (forward) was developed from a computer program in Visual Basic Excel® to simulate the temperature profiles and finally the simulated values ​​were compared with the experimental values. The thermal diffusivity values ​​were obtained using the heating curve of the samples at temperatures of 70 °C. The equivalent diameter value was 7,6536 cm. The experimental value of the thermal diffusivity (α) of the potato was 1,49 x10-7 m2/s  which is within the expected range for roots and tubers. Likewise, the simulated temperature profiles were compared with the experimental temperature profiles in distinct positions, and it was found that the central temperature managed to fix with the temperature in the center of the potato with an error level between 1.37% and 7, 83%.